Socio-economic status and financial burden among hemodialysis patients in Hospital Universiti Sains Malaysia - Fadzli, Nur Fatin Aqilah Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Financial burden among hemodialysis patients were differed according to their socioeconomic status. Different in terms of employment rate, income class and salary determined which class of financial burden patients had. This study aimed to study the effect of socioeconomic status and financial burden among hemodialysis patients at Hospital USM. This study was conducted among 100 participants by using selfadministrated questionnaire. It is conducted from October 2020 to July 2021. The general objective for this study was to study the effect of socioeconomic status and financial burden among hemodialysis patients in Hospital USM. In addition, this study also was conducted to determine the relationship of socioeconomic status and financial burden among hemodialysis patients in Hospital USM. The test used was descriptive statistics and Pearson’s Chi Square test using Statistical Package of Social Sciences (SPSS) version 24.0. Results showed majority of the participants had moderate financial burden (n= 52, 52%). The remaining financial burden which are low and high had equivalent percentage of participants. There was a significant association of socioeconomic status (employment status, salary, and income class) and financial burden among hemodialysis patients in Hospital USM (p > 0.05 and p< 0.05). Different socioeconomic status showed that not everyone had the same financial burden. Thankfully, government had supported the fees for the treatment. The funding automatically reduces some of the burden of participant. Researcher hopes that government and more NGOs could lend their hands towards participant who needs it. This generosity should be carry on for the next generations.